Bridging Theory and Practice: The Role of Experiential Learning and Mentorship in Enhancing the Transition from University to High-School Teaching for Pre-Service English Teachers - Thinh, Mai Phuc (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This study investigates the transition of pre-service English teachers from university to high-school teaching, focusing on the challenges of applying theoretical knowledge in practical classroom settings. The research highlights how the integration of experiential learning and mentorship can effectively bridge the gap between theory and practice. Through a qualitative analysis of pre-service teachers in the Mekong Delta region of south-western Vietnam, this study identifies key challenges such as classroom management, student engagement, and the implementation of student-centred teaching methods. It also explores the transformative impact of hands-on teaching experiences and mentor guidance on the professional development of these teachers. The findings suggest that incorporating more experiential learning opportunities and structured mentorship into teacher-education programs can significantly improve pre-service teachers' preparedness for high-school teaching. This study underscores the need for educational reforms that emphasize practical training, alongside theoretical instruction, to enhance the effectiveness of teacher education.